mTOR Signaling in Metabolism and Cancer - Huang, Shile (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The mechanistic/mammalian target of rapamycin (mTOR), a serine/threonine kinase, is a central regulator for human physiological activity. Deregulated mTOR signaling is implicated in a variety of disorders, such as cancer, obesity, diabetes, and neurodegenerative diseases. The papers published in this Special Issue summarize the current understanding of the mTOR pathway and its role in the regulation of tissue regeneration, regulatory T cell differentiation and function, and different types of cancer including hematologic malignancies, skin, prostate, breast, and head and neck cancer. The findings highlight that targeting mTOR pathway is a promising strategy to fight against certain human diseases.